Hubungan antara karakteristik individu dan fungsi paru di posyandu lansia Kecamatan Langowan Timur - Roring, Amanda; Pangkahila, Erwin Adams; Doda, Diana Vanda Daturara (UNIVERSITAS SAM RATULANGI, 2024)
Background: As people age, their lung function changes significantly, increasing the risk of pulmonary diseases such as pneumonia and COPD. Aim: To determine the relationship between individual characteristics and lung function in the elderly integrated healthcare post of the East Langowan District. Methods: Analytic observational study with cross sectional design, involving 55 samples using purposive sampling. Data analysis was performed using the Lambda Test (gender), Chi-Square (age, BMI [body mass index], and lung disease), and logistic regression analysis. Result: Gender showed a significant association with lung function (p=0.022), where more women had normal lung function than men. Age (p=0.883), BMI (p=0.550), and lung disease (p=0.528) did not show a significant relationship with lung function. Conclusion: There is relation between individual characteristics and lung function in the elderly integrated healthcare post of the East Langowan District. Keywords: lung function, elderly, characteristics